Shota Rustaveli’s Theory of Friendship - Bert Beynen (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2015)
Bert Beynen's article examines the theory of friendship in Shota Rustaveli's twelfth-century epic poem The Knight in the Panther's Skin (Vepkhistkaosani). Beinen argues that the friendship between Avtandil and Tariel serves as the poem's central driving force, propelling the narrative forward in ways that distinguish it from typical courtly romance literature. Drawing on Aristotelian philosophy, Beinen demonstrates how Avtandil becomes Tariel's "second self," assuming responsibility for achieving Tariel's goals when Tariel himself cannot. This friendship enables a remarkable transformation: Tariel evolves from impulsive, instinctive reasoning—what Greek philosophy characterized as "animal" cognition—to rational, deliberative thought associated with "human" cognition. Through Avtandil's influence and their deepening bond, Tariel acquires the capacity for strategic planning, ultimately devising a superior plan for rescuing Nestan-Darejan. Beynen traces an evolution in how the poem depicts friendship itself. The relationship begins within an Aristotelian framework, where one friend substitutes for and mirrors the other. However, it gradually transitions toward a more modern, egalitarian partnership characterized by collaboration and mutual contribution to decision-making. This progression, Beynen suggests, reflects the poem's broader movement from conventional courtly romance tropes toward more contemporary relational dynamics.